Examining self-regulated learning through a social networking ePortfolio in higher education. (23rd August 2019) - Alexiou, Aikaterini; Paraskeva, Fotini
The use of social media applications can have negative effects on performance and as a result the need for interventions supporting learners to self-monitor, manage technology use and academic performance is pressing. The main focus of this research is the implementation of an ePortfolio through a course in higher education for empowering students to manage their academic path. An ePortfolio, as a dynamic social networking tool, was developed along the lines of self-regulated learning (SRL) with the aim of influencing student's self-regulatory capacity. To satisfy the purpose of the study a paired-samples t-test and correlations were employed to explore statistical differences on the levels of SRL processes. The findings reveal that there is a significant increase on the means across SRL processes. Future research needs to explore SRL effects on learning in the context of an ePortfolio using a set of assessment tools for capturing learning outcomes with greater precision.